Analysis of Factors that Influence Public Policy - Siregar, Muklis (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2024)
Public Policy is a number or several government activities carried out to solve a problem in society. Public policy is a rule made to bind our lives as a society, which regulates the rights and obligations of citizens in a country. Public policy can also be interpreted as a decision taken by the government to resolve certain problems that exist in society, both in certain fields and in the general public. In terms of terminology, the meaning of public policy has many meanings. It all depends on the angle one interprets it from. Public policy is an authority that the government has. This authority is exercised to carry out its duties and functions in relation to society. Not only with the community, but this authority is also exercised in relation to the business world. Basically, government policy in organizing people's lives in many aspects of life is a policy that is oriented towards the interests of the community itself. In every public policy, it will begin with the formulation of the problem. The factors that influence public policy in this article include political, religious, educational and racial factors.